Distinct determinants on collagen support alpha 2 beta 1 integrin-mediated platelet adhesion and platelet activation. - Santoro, S A (1991)
Recent studies have revealed that the sequence of amino acids asp-gly-glu-ala represents an essential determinant of the site within the alpha 1(I)-CB3 fragment of collagen recognized by the alpha 2 beta 1 integrin cell surface collagen receptor (Staatz et al., 1991). Studies employing chemical modifications of collagen amino acid side chains confirm both the essential nature of the acidic side chains of aspartic acid and glutamic acid residues and the nonessentiality of lysine epsilon-amino groups in supporting adhesion mediated by the alpha 2 beta 1 integrin. The approach also indicates the presence of a distinct determinant on collagen separate from the alpha 2 beta 1 recognition site that contains essential lysine side chains and that is necessary for subsequent interactions with the platelet surface that give rise to collagen-induced platelet activation and secretion. The two-step, two-site model for cellular signaling involving both an integrin and a signal-transducing coreceptor suggested by these data may be common to other integrin-mediated processes.